Ijen Tourism Cluster (ITC): Analisis Klaster Pengembangan Ekowisata Taman Wisata Alam Kawah Ijen - Joshi Maharani Wibowo (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
Ijen Tourism Cluster (ITC) is a concept to developing economic and tourism activities by expanding and developing tourism destinations around Ijen National Park. ITC uses the natural and social capital found in tourism destination areas to create sustainable tourism activities in the Ijen Crater Nature Park area. This research was conducted to develop a tourism cluster based on a sustainable tourism strategy that integrates natural attractions and local communities' potential applications. The research showed three main problems of ITC applications for tourism activities around Ijen Crater Nature Park. These problems occurred because local communities cannot manage village-owned enterprises (BUMDes) and joint village-owned enterprises (BUMDesa Bersama) optimally; tourists' length of stay around Ijen National Park was short; and cluster integration between tourism areas around the Ijen National Park is poor. This research provides a solution to that problem by creating and developing a creative hub to overcome this problem. The creative hub in the ITC area functioned as a local community's innovation and creativity facilities and a center for educational facilities and strengthening Ijen National Park tourism competitiveness. In the future, the creative hub in this area will become the center of economic activity, education, and environmental conservation for local communities and tourists.